Actin subversion for productive Plasmodium hepatocyte invasion - Frischknecht, Friedrich; Enninga, Jost (Trends in parasitology, 2023)
Productive invasion of hepatocytes by Plasmodium sporozoites is a key step of infection. The parasites traverse hepatocytes before targeting one of them to form a parasitophorous vacuole for parasite expansion. Schepis et al. show the induction of membrane ruffling via host Rho GTPases by Plasmodium sporozoites facilitating productive invasion.